النظام المحاسبي في المصرف التجاري السوري وأفاق تطويره (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تنبع أهمية الأنظمة المحاسبية المطبقة في المصارف من كونها تشكل أساساً لتسجيل ومعالجة العمليات المصرفية؛ هذا ويلعب المصرف التجاري السوري ( كأحد أهم مصارف القطاع العام العاملة في سوريا) دوراً كبيراً في العمليات المصرفية المتعلقة بالتجارة الدولية، ومن هنا تأتي أهمية دراسة واقع النظام المحاسبي المطبق فيه وضرورة تحديث هذا النظام لضمان نوعية ما ينتجه من معلومات محاسبية تستخدم لتقييم نشاط المصرف لاسيما في ظل التحديات الاقتصادية الراهنة وما تقتضيه من دخول سوق المنافسة. إن التحديث المطلوب يجب أن يكون مستمرا، متلائماً مع احتياجات البنك، متناسباً مع متطلبات إعادة تشكيل القطاع المصرفي في ضوء مشروع سوق الأوراق المالية الجديد في سوريا ومنسجماً مع التطورات الهائلة في المصارف العالمية. وبناء عليه فإن البحث يتناول آلية ومنهجية تطوير النظام المحاسبي الموحد المطبق في المصرف التجاري السوري في ضوء التشغيل الالكتروني للبيانات المحاسبية وأتمتة النظام المحاسبي وبما يتلاءم مع متطلبات معايير المحاسبة الدولية ذات الصلة. The importance of accounting systems applied in banks emerges from being a basis of banking transactions. Being one of the most important public sector banks in Syria, the Syrian Commercial Bank plays a great role in banking transactions to do with international trade- hence the significance of the accounting system being used. It is important to update this system in such a way that guarantees the quality of the accounting information provided for assessing the bank’s performance, especially in the light of  the requirements of recent economic challenges for entering the competition market; the modernization required must be continuous, in conformity with bank’s needs,  and with the reconstruction requirements  for the  banking sector in the light of the new Syrian stock exchange project,  taking into account  the huge developments in international banks. According to this, this paper deals with the electronic operating system for accounting data, and the mechanism of the accounting system development in Syrian banks, meeting the needs of relevant international accounting standards.